Glucose production from oil palm trunk - Syafiqah, Hud (2010)
Glucose is simple sugar (monosaccharide). Glucose is derived from hexanal, a chain of six carbon atoms terminating with an aldehyde group. Glucose is also called an aldohexose. Oil palm (Elaeis guineenis) was first introduced into Malaysia for planning through the Botanical Gardens in Singapore in 1870. Commercial cultivation however, was not initiated until 1917. Since oil palm trunks can still be rather moist at the time of felling it was deemed appropriate to initiate a project on the feasibility of using palm trunks for the production of glucose. The objective of this experiment is to produce glucose from oil palm trunk by using acid hydrolysis. The parameter that have been used in this experiment is concentration of acid hydrolysis, pH and concentration of oil palm trunk using Response Surface Methodology (RSM) based on central composite design (CCD). Method that been using for this experiment is acid hydrolysis, hydrolysis of αcellulose by H2SO4 is a heterogeneous reaction is influenced by physical factors. The twenty experiments have been designed by RSM for analysis. The results show there is interaction between the parameter which is pH and acid sulfuric concentration proportional to glucose concentration, acid sulfuric concentration and oil palm trunk concentration proportional to glucose concentration and the last one between pH, oil palm trunk concentration and glucose concentration. For the optimize condition, RSM predicted the best condition of parameters were 66.46% of concentration of acid sulfuric, 5.19 of pH and 0.09 g/ml of concentration of oil palm trunk with the glucose production predicted 3.43629. Based on this condition, the actual production of glucose is 3.445 and the error is 0.25%.